Enantioselective synthesis of BMS-911278: a triple reuptake inhibitor. Issue 1 (15th January 2017) - Li, Jianqing; Smith, Daniel; Krishnananthan, Subramaniam; Wu, Dauh-Rurng; Sun, Dawn; Li, Peng; Ryan, Kristen; Hu, Min; Cui, Wenge; Naginskaya, Jennifer; Liu, Shuang; Lobben, Paul C.; et al.
Graphical abstract: Abstract: BMS-911278 was identified as a potent triple reuptake inhibitor potentially useful for the treatment of depression. The original racemic synthesis suffered from tedious and low recovery resolution and HPLC separation, as well as low-yielding hazardous N -demethylation at the API step. To support further preclinical studies, a scalable enantioselective synthesis was developed. Herein, we report an efficient asymmetric synthesis ofBMS-911278 featuring two key steps: an enantioselective Miyaura reaction and an intramolecular regioselective cyclization. Abstract : ( S )- tert -Butyl 3-(4-bromophenyl)-3-(3-chloro-4-fluorophenyl)propanoate: C19 H19 BrClFO2 [ α ]D 20 = −6.0 ( c 2.55, MeOH) Source of chirality: the intermediate Absolute configuration: 3-( S ) Abstract : ( S )-3-(4-Bromophenyl)-3-(3-chloro-4-fluorophenyl)propanoic acid: C15 H11 BrClFO2 [ α ]D 20 = −2.6 ( c 7.20, DMSO) Source of chirality: the intermediate Absolute configuration: 3-( S ) Abstract : ( S )-3-(4-Bromophenyl)-3-(3-chloro-4-fluorophenyl)propanamide: C15 H12 BrClFNO [ α ]D 20 = −6.1 ( c 5.70, MeOH) Source of chirality: the intermediate Absolute configuration: 3-( S ) Abstract : ( S )-(3-(4-Bromophenyl)-3-(3-chloro-4-fluorophenyl)propanamido)methylacetate: C18 H16 BrClFNO3 [ α ]D 25 = −3.8 ( c 5.70, MeOH) Source of chirality: the intermediate Absolute configuration: 3-( S ) Abstract : ( R )-8-Bromo-5-(3-chloro-4-fluorophenyl)-4, 5-dihydro-1 H -benzo[ c ]azepin-3(2 H )-one: C16 H12 BrClFNO [ α ]D 20 = −75.85 ( c 3.39, MeOH) Source of chirality: the intermediate Absolute configuration: 3-( R ) Abstract : ( R )-8-Bromo-5-(3-chloro-4-fluorophenyl)-2, 3, 4, 5-tetrahydro-1 H -benzo[ c ]azepine: C16 H14 BrClFN [ α ]D 25 = −75.85 ( c 3.39, MeOH) Source of chirality: the intermediate Absolute configuration: 3-( R ) Abstract : tert -Butyl ( R )-8-bromo-5-(3-chloro-4-fluorophenyl)-1, 3, 4, 5-tetrahydro-2 H -benzo[ c ]azepine-2-carboxylate: C21 H22 BrClFNO2 [ α ]D 20 = −75.85 ( c 3.39, MeOH) Source of chirality: the intermediate Absolute configuration: 3-( R ) Abstract : tert -Butyl ( R )-5-(3-chloro-4-fluorophenyl)-8-(6-(trifluoromethyl)pyridazin-3-yl)-1, 3, 4, 5-tetrahydro-2 H -benzo[ c ]azepine-2-carboxylate: C26 H24 ClF4 N3 O2 [ α ]D 20 = −51.9 ( c 3.70, MeOH) Source of chirality: the intermediate Absolute configuration: 3-( R ) Abstract : ( R )-5-(3-Chloro-4-fluorophenyl)-8-(6-(trifluoromethyl)pyridazin-3-yl)-2, 3, 4, 5-tetrahydro-1 H -benzo[ c ]azepine: C21 H16 ClF4 N3 [ α ]D 20 = −9.4 ( c 3.01, MeOH) Source of chirality: the product Absolute configuration: 3-( R ) Abstract : ( R )-5-(3-Chloro-4-fluorophenyl)-8-(6-(trifluoromethyl)pyridazin-3-yl)-2, 3, 4, 5-tetrahydro-1 H -benzo[ c ]azepinel -tartrate: C21 H16 ClF4 N3 ·0.85 M tartrate salt and 1.0 M hydrate [ α ]D 20 = +10.8 ( c 1.54, 50/50 MeOH/H2 O) Source of chirality: the product Absolute configuration: 3-( R )